Faktor risiko kontaminasi bakteri Salmonella spp. pada ikan bandeng (Chanos chanos) di Pasar Banguntapan Yogyakarta - Ubaidillah Ubaidillah; Syifa Urrokmah Roe (STIKes Surya Global Yogyakarta, 2022)
Milkfish is known as brackish water fish which is often consumed by the public and has a high protein value. In addition to high nutritional content, milkfish also contains pathogenic bacteria that can cause disease in humans. The presence of these bacteria can affect the quality of fish, especially Salmonella Spp. These bacteria are pathogenic bacteria that can cause disease in humans. Pollution of Salmonella Spp bacteria on milkfish can be caused by environmental cleanliness, handling and marketing processes. The purpose of this study is to determine risk factors of Salmonella spp.bacterial contamination on milkfish in market Banguntapan District Yogyakarta. This research was quantitative research using a cross sectional approach, the population in this study were all milkfish merchants in the market Banguntapan district. The sampling technique used purposive sampling technique, the number of samples were 24 traders. From the results of data analysis there was a significant correlation between environmental factors, hygiene factors and seller activity and pH factors, on Salmonella Spp. bacteria in milkfish (Chanos chanos) There was no significant effect between the temperature factor variables on the contamination of Salmonella Spp. in milk fish (Chanos chanos) with a p value of (1,000 0.05).